A content analysis of servant leadership studies - Yigit, Burcu; Bozkurt, Serdar (CANADIAN INST KNOWLEDGE DEVELOPMENT - CIKD, 2017)
The aim of this study was to evaluate the articles has been written about servant leadership between 2000 and 2016 years (until August). For this purpose, four world-known electronic databases were identified in this study. These databases are EBSCO (F = 35), Sage (F = 26), Science Direct (F = 8) and Emerald (F = 27). Generally, 96 articles were gathered from these databases about servant leadership. These articles were analyzed according to journal name, publication year, country, sample size, type of research, data collection tool(s), and data analysis method. Using the content analysis method, the frequency distribution of data, descriptive statistics, and percentage analysis were determined. When the results of the study were examined, it was concluded that the most published journal was Leadership and Organizational Development Journal during 2015 and 2016 in the United States. The sample size ranged from 1 to 500. To collect data, quantitative research and survey were used. Factor analysis, correlation, and regression analysis were used to analyze the obtained data. (C) AIMI Journals
Keywords: Servant Leadership; Content Analysis; COMMITMENT; Business & Economics